Landscape Ecological Risk Assessment for the Tarim River Basin on the Basis of Land-Use Change - Guangyao Wang; Guangyan Ran; Yaning Chen; Zhengyong Zhang (Remote Sensing, 2023)
Land-use variation indicates the spatial differentiation of regional ecological risk. Landscape ecological risk assessment (LERA) has been used for the measurement and prediction of environmental quality. In the present study, the land-use dynamics of the Tarim River Basin from 2000 to 2020 were quantitatively analyzed using ENVI 5.6 software based on Landsat TM and ETM+ images (2000, 2010, and 2020). Moreover, the ecological risk level and its spatiotemporal differentiation features were explored using geostatistical methods based on landscape pattern indices. The results show that: (1) From 2000 to 2020, the arable land area increased the most (12,130.272 km2), and the woodland, wetland, water bodies, and building-land areas increased by 2416.541 km2, 4103.789 km2, 3331.230 km2, and 2330.860 km2, respectively. However, the bare-land area decreased the most (18,933.943 km2). (2) From 2000 to 2020, a decrease was detected in the landscape ecological risk index (LERI) of the basin, and the very low-, low-, and moderate-risk areas had the largest decrease. In addition, the area of the low- and moderate-risk areas gradually increased, while that of the high-risk areas was reduced. (3) The conversion rate of low-risk areas to very low-risk areas was the largest (5144.0907 km2/a), followed by that of high-risk areas to moderate-risk areas (4994.4765 km2/a). Therefore, the overall landscape ecological risk (LER) of the basin was reduced from 2000 to 2020, but the ecological risk of some areas, especially that of the glaciers and permanent snow-covered areas, still needs close attention.